Feasibility of free‐breathing 19F MRI image acquisition to characterize ventilation defects in CF and healthy volunteers at wash‐in - Chung, Sang Hun; Huynh, Khoi Minh; Goralski, Jennifer L.; Chen, Yong; Yap, Pew‐Thian; Ceppe, Agathe S.; Powell, Margret Z.; Donaldson, Scott H.; Lee, Yueh Z. (Magnetic resonance in medicine, 2023)
Purpose To explore the feasibility of measuring ventilation defect percentage (VDP) using 19F MRI during free‐breathing wash‐in of fluorinated gas mixture with postacquisition denoising and to compare these results with those obtained through traditional Cartesian breath‐hold acquisitions. Methods Eight adults with cystic fibrosis and 5 healthy volunteers completed a single MR session on a Siemens 3T Prisma. 1H Ultrashort‐TE MRI sequences were used for registration and masking, and ventilation images with 19F MRI were obtained while the subjects breathed a normoxic mixture of 79% perfluoropropane and 21% oxygen (O2). 19F MRI was performed during breath holds and while free breathing with one overlapping spiral scan at breath hold for VDP value comparison. The 19F spiral data were denoised using a low‐rank matrix recovery approach. Results VDP measured using 19F VIBE and 19F spiral images were highly correlated (r = 0.84) at 10 wash‐in breaths. Second‐breath VDPs were also highly correlated (r = 0.88). Denoising greatly increased SNR (pre‐denoising spiral SNR, 2.46 ± 0.21; post‐denoising spiral SNR, 33.91 ± 6.12; and breath‐hold SNR, 17.52 ± 2.08). Conclusion Free‐breathing 19F lung MRI VDP analysis was feasible and highly correlated with breath‐hold measurements. Free‐breathing methods are expected to increase patient comfort and extend ventilation MRI use to patients who are unable to perform breath holds, including younger subjects and those with more severe lung disease.